The M/G/1 queue system with random vacation. (19th May 2019) - Lv, Sheng-Li; Lyu, You; Sun, Xiao-Chen
ABSTRACT: The vacation queue models have been studied by many researchers. They usually assume that the server will take a vacation immediately at the end of a busy period. But in some cases, it is random that the server takes a vacation when the system is empty. Therefore, we study an M/G/1 queue model with random vacation policy in this paper. We derive the indexes such as the mean queue length, mean sojourn time of customers and the busy period of the server. Finally, numerical examples are provided for illustration.